Advances in Research on Water Resources and Environmental Systems Selected papers of the 2nd International Conference on Geo-Spatial Technologies and Earth Resources 2022 - Vo, Phu Le.; Tran, Dang An.; Pham, Thi Lan.; Le Thi Thu, Ha.; Nguyen Viet, Nghia (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book composes the proceedings of the international Conference on Geo-Spatial Technologies and Earth Resources (GTER 2022) which was co-organized by Hanoi University of Mining and Geology and the International Society for Mine Surveying (ISM) held at Hanoi city on October 13-14, 2022. GTER 2022 is technically co-sponsored by Vietnam Mining Science and Technology Association (VMST), Vietnam Association of Geodesy, Cartography and Remote Sensing (VGCR), Vietnam National Coal-Mineral Industries Holding Corporation Limited (VINACOMIN), and the Dong Bac Corporation (NECO). GTER 2022 aims to bring together experts, researchers, engineers, and policymakers to discuss and exchange their knowledge and experiences in recent advances research water resources and environmental systems.
Application of MODFLOW-based SEAWAT code for seawater intrusion forecasting into the Upper Pliocene coastal aquifer in the Ca Mau Peninsula, Southern Vietnam -- Seawater Intrusion Processes along the Tien river Mouth in the Period 2000-2020 -- Developing software package for 2D modeling hydrodynamics and salinity transport in Cu Lao Dung, Mekong Delta -- An Assessment of Some Algorithms for Modeling and Forecasting Horizontal Displacement of Ialy Dam, Vietnam -- Simulation of The Hydrodynamic Regime of Aquaculture Development Zones within Binh Dinh, Vietnam -- Prediction of Suspended Sediment Concentration By Artificial Neural Networks At The Vu Gia-Thu Bon Catchment, Vietnam -- Criteria affecting groundwater potential: A Systematic Review of Literature -- Pumped Storage Power Plant, Solutions to Ensure Water Sustainability and Environmental Protection -- Modelling the influences of river water level on the flooding situation of urban areas: a case study in Hanoi, Vietnam -- 188 Assessing the current characteristics of concrete in some parts Hoa Binh hydropower plant -- Hydraulic Performance of a Sand Trap in The Flushing Period to Support The Maintenance of The Pengasih Irrigation Network, Indonesia -- Identification of hydrogeochemical processes and controlling factors in groundwater and surface water using integrated approaches, Tuul River basin (Ulaanbaatar, Mongolia).-Application of plant endogenous microorganisms (endophytes) in the treatment of heavy metal pollution in soils -- Evaluation of Density Characterization of Municipal Solid Waste in Southern Part of Vietnam -- Assessment of Lead (Pb) Accumulation in Native Plants Growing on Coal Mine Site in Northeastern Vietna.
Keywords: Earth sciences; Geography; Environmental education; Environmental management; Refuse and refuse disposal; Financial risk management; Environmental protection; Civil engineering; Earth and Environmental Sciences; Environmental and Sustainability Education; Environmental Management; Waste Management/Waste Technology; Risk Management; Soil and Water Protection